(untitled) - Dukkipati, Rao V. (Oxford, 2007)
This book is designed a supplement to standard texts in linear Mechanical Vibrations. Emphasis is placed on the funddamentals with discussions and problems. Each chapter begins with statements of pertinent definitions and principles. This is followed by solved and supplenentary problems...
Keywords: automatic control,vibration